2016
DOI: 10.1002/2015jd024407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified soil water‐heat physics on RegCM4 simulations of climate over the Tibetan Plateau

Abstract: To optimize the description of land surface processes and improve climate simulations over the Tibetan Plateau (TP), a modified soil water‐heat parameterization scheme (SWHPS) is implemented into the Community Land Model 3.5 (CLM3.5), which is coupled to the regional climate model 4 (RegCM4). This scheme includes Johansen's soil thermal conductivity scheme together with Niu's groundwater module. Two groups of climate simulations are then performed using the original RegCM4 and revised RegCM4 to analyze the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 74 publications
(146 reference statements)
2
33
0
1
Order By: Relevance
“…Observations (OBS) are the same as Figure . RegCM4_OC and RegCM4_RC indicate RegCM4 coupled with the original CLM3.5 and the revised CLM3.5, respectively (after Wang et al , ). [Colour figure can be viewed at wileyonlinelibrary.com].…”
Section: Recent Progress Of Precipitation On the Tp From Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Observations (OBS) are the same as Figure . RegCM4_OC and RegCM4_RC indicate RegCM4 coupled with the original CLM3.5 and the revised CLM3.5, respectively (after Wang et al , ). [Colour figure can be viewed at wileyonlinelibrary.com].…”
Section: Recent Progress Of Precipitation On the Tp From Observationsmentioning
confidence: 99%
“…DDMs, which can describe climate variations induced by mesoscale and smaller topography, underlying surface characteristics, and other factors, have become an outstanding tool for comprehending climate characteristics and change, such as precipitation and its response to atmospheric circulation (e.g. Giorgi, 1990;Wang et al, 2004Wang et al, , 2016Gao et al, 2011Gao et al, , 2015bMaussion et al, 2014;Feng and Zhou, 2015). Of the various DDMs that have been applied over the TP region, the Regional Climate Model (RegCM) series (Pal et al, 2007;Giorgi et al, 2012) are the most commonly used.…”
Section: Precipitation Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicated that the performance of RCMs can be significantly influenced by the parameterization of the land surface model (LSM), including surface albedo, soil water–heat transfer, snow properties, vegetation fluctuations, and other factors (Davin and Seneviratne, 2012; Gao et al, 2017; Hong et al, 2009; Jin et al, 2010; Rechid et al, 2009; Wang et al, 2016). For the TP, researchers have tested the applicability of many different LSMs during the past decade (Cuo et al, 2015; Gao et al, 2004; Guo and Wang, 2013; Guo et al, 2011; Wang et al, 2016), including the revised Simple Biosphere model (Sellers et al, 1996a), the variable infiltration capacity model (Liang et al, 1994), the simultaneous heat and water model (Flerchinger and Saxton, 1989), Version 4 of the Community Land Model (Oleson et al, 2010), and others. Of all the relevant processes, surface energy partitioning is the most fundamental and has attracted considerable research interests (Gao et al, 2004, 2017; Guo et al, 2011; Wang et al, 2016; Yang et al, 2009).…”
Section: Mathematical Expressions Relating the Soil Albedo To The Solmentioning
confidence: 99%